AL-MUSNAD OF AHMAD IBN HANBAL AND THE REFUTATION OF MU’TAZILAH IDEOLOGY: A Study of Hadith as Intellectual Resistance (RIWAYAH, 2025)
This study examines the work of Ahmad ibn Hanbal, al-Musnad, as an instrument of intellectual and theological resistance to Muʿtazilite rationalism during the mihnah of the third Hijri century. By situating the work within its historical and socio-political context, the study employs qualitative analysis of hadiths in al-Musnad of Ahmad ibn Hanbal that address God’s knowledge, predestination (qadar), divine justice (al-ʿadl), and the ontological status of the Qur’an. The findings demonstrate that Ahmad ibn Hanbal’s codification of hadith was not merely preservative in nature, but rather constituted a deliberate epistemological response aimed at reaffirming the primacy of revelation (naql) over speculative reason (ʿaql) as promoted by the Muʿtazilah. By positioning the Prophetic tradition as the supreme authority, Ahmad ibn Hanbal challenged core Muʿtazilite doctrines, such as the denial of the eternality of God’s attributes and the doctrine of the createdness of the Qur’an, while simultaneously constructing a coherent Sunni theological framework grounded in submission to the absolute will of God. Moreover, Ahmad ibn Hanbal’s steadfastness in the face of political pressure and persecution conferred moral authority upon the hadiths he transmitted and reflects a strong dimension of living hadith. The contribution of this study lies in its argument that al-Musnad of Ahmad ibn Hanbal functions not only as a scholarly corpus, but also as a socio-religious manifesto that significantly contributed to the consolidation of Sunnite theology. [Penelitian ini mengkaji karya Ahmad bin Hanbal yang berjudul al-Musnad sebagai instrumen perlawanan intelektual dan teologis terhadap rasionalisme Muʿtazilah pada masa mihnah abad ketiga Hijriah. Dengan menempatkan karya tersebut dalam konteks historis serta sosio-politik zamannya, penelitian ini menggunakan analisis kualitatif terhadap hadis-hadis pada al-Musnad Ahmad bin Hanbal yang berkaitan dengan ilmu Allah, takdir (qadar), keadilan Ilahi (al-ʿadl), dan status ontologis Al-Qur’an. Hasil penelitian menunjukkan bahwa kodifikasi hadis yang dilakukan oleh Ahmad bin Hanbal tidak semata-mata bersifat preservatif, melainkan merupakan respons epistemologis yang disengaja untuk menegaskan kembali primasi wahyu (naql) atas rasio spekulatif (ʿaql) yang dikedepankan oleh Muʿtazilah. Dengan menempatkan tradisi kenabian sebagai otoritas utama, Ahmad bin Hanbal menantang doktrin-doktrin pokok Muʿtazilah, seperti penolakan terhadap keabadian sifat-sifat Allah dan paham kemakhlukan Al-Qur’an, sekaligus membangun kerangka teologi Sunni yang koheren dan berakar pada ketundukan terhadap kehendak Allah yang absolut. Selain itu, keteguhan Ahmad bin Hanbal dalam menghadapi tekanan dan penganiayaan politik memberikan otoritas moral pada hadis-hadis yang diriwayatkannya, sekaligus mencerminkan dimensi living hadis yang kuat. Kontribusi penelitian ini terletak pada argumentasi bahwa al-Musnad Ahmad bin Hanbal tidak hanya berfungsi sebagai korpus keilmuan, tetapi juga sebagai manifesto sosio-keagamaan yang berkontribusi signifikan terhadap penguatan konsolidasi teologi Sunni.]